Case report: The first account of undifferentiated sarcoma with epithelioid features originating in the pleura - Xiao, Ling-Xi; Liu, Li; Deng, Wang (Frontiers in Medicine, 2024)
Undifferentiated epithelioid sarcoma (USEF) is a rare subtype of undifferentiated soft tissue sarcoma that presents unique challenges in clinical diagnosis and treatment. Here, we report a case of USEF occurring in the pleura of a 51-year-old man for the first time. Thoracoscopic examination revealed widespread nodular changes, and pathological analysis confirmed the presence of numerous epithelioid atypical cells. Immunohistochemical (IHC) analysis demonstrated an undifferentiated phenotype with distinct characteristics: epithelial membrane antigen (foci +), vimentin (+), Ki-67 (+70% +), TTF-1 (+), P53 (mutant type +90%), INI-1 (+), and CK5/6 (small foci +). Immunohistochemical examination of the tumor showed that the tumor was an undifferentiated epithelioid sarcoma. High-throughput DNA sequencing revealed pivotal mutations, including a nonsense mutation in the NF1 gene (c.641A>G(p.H214R)). and critical TP53 missense mutation (c.641A>G(p.H214R)). This TP53 mutation, with a tumor mutation burden of 16.5 Muts/Mb, signifies a high level of genomic instability, likely contributing to the rapid progression and aggressiveness of the disease. Detection of the TP53 mutation provides essential insights, indicating the disease’s rapid progression and highlighting the potential for targeted therapies. Although the patient's disease progressed extremely rapidly and he tragically died within a week, we discussed the results of IHC and DNA sequencing in detail and discussed his possible treatment options. Insights gained from this case will be critical in shaping future diagnostic and therapeutic paradigms for USEF, particularly in the context of TP53 mutations.